1987
DOI: 10.1111/j.1469-7998.1987.tb04473.x
|View full text |Cite
|
Sign up to set email alerts
|

The infrastructure of aesthetes in Tonicella marmorea (Polyplacophora; Ischnochitonina) and a new functional hypothesis

Abstract: With 8 plates and 1 figure in the text) The valve surface morphology and aesthete ultrastructure of Tonicella marmorea is described. The possible functions of these very numerous organs are considered with particular reference to the ecological needs of the animal and their similarity to other invertebrate organs. A periostracum-secreting function is proposed as an alternative to the more commonly postulated light receptor theory. PLATE 111. (a) Dorsal surface of an apical cap showing the layer of periostracum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…A large proportion of the light striking the dorsal surface of the valve will be reflected or absorbed by the properiostracum and tegmentum and only a limited amount will penetrate the valve layers to reach the megalaesthete. In addition, the hypothesis proposed by Baxter et al (1987) and further promoted by Baxter et al (1990) and Sturrock & Baxter (1993) that the aesthetes may in some way be monitoring and repairing the thickness and integrity of the properiostracum is not unreasonable. Dual function receptors of this type are not unique, and in describing the eyes of Pecten maximus L., Barber, Evans & Land (1967) suggested that the distal cells which have ciliarly derived receptors, and can be presumed analogous to the C. achatinus rhabdomer, function in shadow response, whereas the proximal cells, comparable to the myeloid body, monitor light intensity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A large proportion of the light striking the dorsal surface of the valve will be reflected or absorbed by the properiostracum and tegmentum and only a limited amount will penetrate the valve layers to reach the megalaesthete. In addition, the hypothesis proposed by Baxter et al (1987) and further promoted by Baxter et al (1990) and Sturrock & Baxter (1993) that the aesthetes may in some way be monitoring and repairing the thickness and integrity of the properiostracum is not unreasonable. Dual function receptors of this type are not unique, and in describing the eyes of Pecten maximus L., Barber, Evans & Land (1967) suggested that the distal cells which have ciliarly derived receptors, and can be presumed analogous to the C. achatinus rhabdomer, function in shadow response, whereas the proximal cells, comparable to the myeloid body, monitor light intensity.…”
Section: Discussionmentioning
confidence: 98%
“…The debate as to the true function/s of the aesthetes in chitons has been ongoing since Moseley (1885) first described these structures and referred to them as 'eyes'. Baxter et al (1987) questioned whether performing a light receptor role was the primary function of aesthetes, arguing instead that the secretion of properiostracum was their principal function. This hypothesis has been further substantiated by Baxter et al (1990) and Sturrock & Baxter (1993), although in these studies and others (Haas & Kriesten, 1978;Fischer & Renner, 1978;Fischer, 1988) it has become increasingly apparent that some sensory function may also be performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The function of the micro‐aesthetes remains unresolved. Baxter et al . (1987), studying Callochiton , suggest a secretory function, but the fact that the subsidiary cap is imperforate led Reindl et al.…”
Section: Polyplacophoramentioning
confidence: 99%